Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1210/jc.2009-0141
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Metabolic Determinants of Plasma PCSK9 Levels

Abstract: Multiple metabolic and genetic factors contribute to variation in plasma levels of PCSK9 in the general population. Although levels of PCSK9 correlate with plasma levels of LDL-C, they account for only a small proportion of the variation in the levels of this lipoprotein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

68
352
11
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 463 publications
(449 citation statements)
references
References 25 publications
68
352
11
10
Order By: Relevance
“…Although positive correlations were observed between plasma PCSK9 and both FPG and HOMA-IR in the Dallas Heart Study [12], we did not find any associations between p.R46L and either FPG, HbA 1c , or markers of insulin resistance (HOMA-IR) or insulin secretion (HOMA-B). However, a non-clinically relevant tendency for a positive association between p.R46L and FPG was observed in MAGIC.…”
Section: Discussioncontrasting
confidence: 96%
“…Although positive correlations were observed between plasma PCSK9 and both FPG and HOMA-IR in the Dallas Heart Study [12], we did not find any associations between p.R46L and either FPG, HbA 1c , or markers of insulin resistance (HOMA-IR) or insulin secretion (HOMA-B). However, a non-clinically relevant tendency for a positive association between p.R46L and FPG was observed in MAGIC.…”
Section: Discussioncontrasting
confidence: 96%
“…As observed in non-diabetic patients [17][18][19], we found that plasma PCSK9 levels positively correlated with TC, LDL-C, non-HDL-C, BMI, ÎłGTP, insulin and HOMA-IR at baseline levels in subjects with impaired glucose tolerance or T2DM. On the other hand, fasting plasma glucose was negatively correlated with plasma PCSK9 levels in our study on impaired glucose tolerance or type 2 diabetes mellitus, which does not appear to be consistent with these reports on non-diabetic patients.…”
Section: Discussionsupporting
confidence: 81%
“…119 In the multiethnic Dallas Heart Study of 3138 patients, plasma PCSK9 levels were significantly higher in women (n=1863) than in men (n=1489). This difference persisted after adjusting for most variables.. 120 In the same study, premenopausal women had considerably higher levels of plasma PCSK9 than postmenopausal women. Estrogen treatment did not significantly affect fasting PCSK9 levels in postmenopausal women.…”
Section: Physiological Modulation Of Pcsk9 Levels Variation With Agementioning
confidence: 83%